Dense Packing of Cerebral Aneurysms: An In Vitro Study with Detachable Platinum Coils - Piotin, Michel; Mandai, Shinya; Murphy, Kieran J.; Sugiu, Kenji; Gailloud, Philippe; Martin, Jean-Baptiste; Rüfenacht, Daniel A. (American Journal of Neuroradiology, 2000)
Summary: Aneurysm models were used to study the density of packing after coil embolization. Platinum coils were introduced until the point of minimally dense packing, indicated by aneurysmal circulatory exclusion. Packing was continued up to the point of maximal density, indicated by protrusion into the parent artery. Volumetric ratios (coil volume/aneurysmal volume) were calculated for minimally and maximally dense packing. Maximally dense packing ratios were a little higher than the minimally dense ratios, but less than 37%.